Evaluasi Penggunaan Antibiotik dengan Metode Gyssens pada Pasien Stroke Rawat Inap di RSUD Koja secara Retrospektif (Periode KJS dan BPJS) - Sitompul, Fransiska; Radji, Maksum; Bahtiar, Anton (Jurnal Kefarmasian Indonesia, 2016)
Stroke is a major cause of mortality and morbidity worldwide. Patients with stroke are susceptible to medical complications, especially infections. This study aim to evaluate antibiotic by stroke inpatients hospitalized in RSUD Koja (KJS and BPJS period) with Gyssens methods. The study design is a retrospective cross-sectional. The sample is consisted of 112 medical records from KJS period (July 2013-December 2013) and 74 medical records from BPJS period (January 2014-June 2014) taken by total sampling. The use of antibiotic were analyzed using Chi Square and logistic regression multivariate. The percentage of antibiotic use was 23,11%, mostly were ceftriaxon 33,3%, ceftizozim 7,6% and amoxicillin – clavulanic acid 7,6%. Length of stay more than 7 days was 77,96%. The most common route of antibiotic administration was parenteral (68,67%). Patients that were given antibiotics were,among others,diagnosal by bronchopneumonia (29,33%), pulmonary tuberculosis and 17,6% and urinary tract infection (8,7%). The clinical outcome showed that 69,3% of 186 patients were recovered after antibiotic were given to treat their infections. Gyssen evaluation method showed that rational antibiotic used on KJS period was 77,4% and BPJS periods was 81,3%. There were correlations between rational use at antibiotic and the route of administration, between clinical outcome anduse at diagnosis and route of administration. The conclusion of this study according to Gyssen method is the rational antibiotic influence the clinical outcome (p < 0,05)